2014
DOI: 10.1016/j.compbiolchem.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic network motifs can provide novel insights into evolution: The evolutionary origin of Eukaryotic organelles as a case study

Abstract: Phylogenetic trees are typically constructed using genetic and genomic data, and provide robust evolutionary relationships of species from the genomic point of view. We present an application of network motif mining and analysis of metabolic pathways that when used in combination with phylogenetic trees can provide a more complete picture of evolution. By using distributions of three-node motifs as a proxy for metabolic similarity, we analyze the ancestral origin of Eukaryotic organelles from the metabolic poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Motifs are patterns with significant higher occurrences in complex networks than in randomized networks . Recent studies have demonstrated that metabolic network motif abundance is related to biochemical functions and able to capture inter‐species differences .…”
Section: Resultsmentioning
confidence: 99%
“…Motifs are patterns with significant higher occurrences in complex networks than in randomized networks . Recent studies have demonstrated that metabolic network motif abundance is related to biochemical functions and able to capture inter‐species differences .…”
Section: Resultsmentioning
confidence: 99%
“…Although the proposition of an endosymbiotic origin of eukaryotes initially met stiff resistance, and several details of the theory presented by Margulis turned out to be incorrect, 1 it has come to be generally accepted. The endosymbiotic theory explains the origin of double-membrane-bound organelles in eukaryotes, and has spurred continued debate about the evolution of other membrane-bound organelles including the nucleus (Embley and Martin, 2006; Devos et al, 2014; Shellman et al, 2014). Interestingly, the third organelles mentioned by Sagan (1967) were the (9+2) basal bodies – assemblies of microtubules found at the base of flagellum and cilium that are essential for mitosis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, [19] shows that genes that are related to highly connected reactions in metabolic networks are subject to stricter evolutionary constraints. Another example is [20] that uses motifs in a metabolic network to study the evolutionary origin of six Eukaryotic organelles. Finally, Reporter Algorithm [3] detects biomarker metabolites, which have the highest dysregulation of gene expression in their direct neighborhood with respect to a phenotype.…”
mentioning
confidence: 99%